2018
DOI: 10.1186/s12889-018-6210-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a co-designed physical activity program for older adults: positive impact when delivered at scale

Abstract: BackgroundDespite known health benefits of physical activity (PA), older adults remain among the least physically active age group globally with 30–60% not meeting guidelines. In Canada, 87% do not meet recommended guidelines. To influence population health, interventions that are effective in small trials must be disseminated at scale. Despite evidence for efficacy, few PA interventions are scaled up to reach the wider community. In 2015, British Columbia (BC) Ministry of Health released a PA strategy where o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(92 citation statements)
references
References 65 publications
2
90
0
Order By: Relevance
“…To address this priority, the Ministry entered into a partnership with the Active Aging Research Team (AART; comprised of university‐based researchers and highly qualified support staff; http://www.activeagingrt.ca). AART undertook a number of province‐wide initiatives to support implementation of programs to increase older adults' PA and social connectedness in community settings (McKay et al). Among them, there was a signature initiative called Choose to Move (McKay et al) and a grant program called Active Aging Grants (AAGs).…”
Section: Introductionmentioning
confidence: 99%
“…To address this priority, the Ministry entered into a partnership with the Active Aging Research Team (AART; comprised of university‐based researchers and highly qualified support staff; http://www.activeagingrt.ca). AART undertook a number of province‐wide initiatives to support implementation of programs to increase older adults' PA and social connectedness in community settings (McKay et al). Among them, there was a signature initiative called Choose to Move (McKay et al) and a grant program called Active Aging Grants (AAGs).…”
Section: Introductionmentioning
confidence: 99%
“…To assess whether PA and social connectedness differed by participants' loneliness status at baseline, we used general linear mixed effects models with time (0, 3, 6 months) as a categorical predictor (29). In model 1 we included sex and baseline loneliness (dichotomous measure; lonely vs. not lonely) as xed effects.…”
Section: Discussionmentioning
confidence: 99%
“…In collaboration with key community stakeholders we scaled up CTM across the province of BC, Canada in three phases [2016][2017][2018][2019][2020]. In Phases 1 and 2 (Jan 2016-May 2017) CTM effectively enhanced PA, mobility, social isolation and diminished feelings of loneliness in older adults (29). Our implementation evaluation demonstrated that CTM could be effectively adapted to context (30) and implemented at scale by trained activity coaches in collaboration with key community recreations organizations with established reach to older adults (29,30).…”
Section: Contextmentioning
confidence: 99%
See 2 more Smart Citations